2020
DOI: 10.1590/0103-6440202003196
|View full text |Cite
|
Sign up to set email alerts
|

Physical-Mechanical Properties of Bulk Fill Composites Submitted to Biodegradation by Streptococcus mutans

Abstract: The aim of this study was to evaluate the Streptococcus mutans biofilm influence on the roughness (Ra), gloss (GU), surface hardness (KHN) and flexural strength (FS) of high viscosity bulk fill composites. Filtek Bulk Fill (FBF), Tetric N Ceram Bulk Fill (TNC), X-tra fil Bulk Fill (XF) and Filtek Z350 (FZ) were used. Ten discs of each composite were prepared for Ra, KHN and GU and 20 bars for the FS. After 24 h, specimens were polished and initial analyzes performed. Samples were sterilized and subjected to bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
1
9
0
2
Order By: Relevance
“…Regarding the hardness analysis, it could be observed that Z250 conventional resin composite showed higher hardness at the 0–1 mm area than BFCs. These results are in accordance with previous findings, where it was found that conventional resin composites had significantly higher hardness values than several BFCs [ 29 30 ]. These results could be related to the presence of aluminum oxide in the Z250 material, also the differences in the organic matrix among the materials, such as the presence of elastic monomers within the BFCs composition, could also have an influence [ 31 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the hardness analysis, it could be observed that Z250 conventional resin composite showed higher hardness at the 0–1 mm area than BFCs. These results are in accordance with previous findings, where it was found that conventional resin composites had significantly higher hardness values than several BFCs [ 29 30 ]. These results could be related to the presence of aluminum oxide in the Z250 material, also the differences in the organic matrix among the materials, such as the presence of elastic monomers within the BFCs composition, could also have an influence [ 31 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…In 29 studies (63%), both Ra and GU were presented. 7,[9][10][11][12][14][15][16]19,[22][23][24][25][26][27]31,32,[38][39][40][41][42][44][45][46][47][48]51 Twelve of these studies (26%) showed a high or moderate inverse correlation between surface smoothness and gloss of resin composites. 9,12,16,19,26,27,32,33,41,44,45,51 Seventeen of the studies (37%) determined no significant correlation between surface roughness and gloss (Table 2).…”
Section: Evaluation Of Surface Roughness (Ra) and Gloss (Gu) Based On...mentioning
confidence: 99%
“…The commercial polishers that produced smoothest surfaces for microfills were Sof-Lex (0.04 μm) and Astropol (0.01 μm), and the polishers that produced glossiest surfaces were PoGo (71 GU), Astropol Twenty-four studies compared suprananofill/nanofill composites to other types of composites such as nanohybrid, microhybrid, hybrid, bulkfill, and flowable. 7,[9][10][11][12][14][15][16][18][19][20]24,26,27,29,32,33,35,37,38,42,44,45,47 In 15 of these studies, suprananofill and nanofilll composites presented smoother surfaces with Ra values ranging from 0.001 to 0.8 μm. The composite materials that presented the smoothest surfaces were Filtek Supreme, Estelite and Enamel Plus HFO.…”
Section: Evaluation Of Surface Roughness (Ra) and Gloss (Gu) Based On...mentioning
confidence: 99%
“…Gloss and surface roughness are usually linked together, and the relationship between the two has been illustrated in previous studies [ 18 , 38 ]. Tunac et al [ 39 ] showed how filler size, distribution, geometry, and volume fraction could influence the polishing ability of composites, improving with smaller particle size and higher filler loading.…”
Section: Discussionmentioning
confidence: 97%
“…A rougher surface loses its glossy aspect, affecting the esthetics of the restoration [ 17 ]. The softening of the organic matrix increases the wear exposure of inorganic fillers and their displacement, creating pores that increase biofilm accumulation and staining [ 18 , 19 ]. Examples of these most common agents are coffee, wine, tobacco, ethanol, and different kinds of oils available in the regular human diet [ 20 ].…”
Section: Introductionmentioning
confidence: 99%